IF IT'S A WOMAN, THE WORLD IS BRIGHT - Khoshimova , Shakhlo (PT. Antis International Publisher, 2024)
In this article, the authors present various information on achieving gender equality for women in our country and increasing their status in the social and political spheres. The authors hope that the accumulated experience will be useful to both readers and specialists